2011
DOI: 10.2174/092986711797636063
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic Proteasome Inhibitors

Abstract: Proteasome inhibitors have proven to be effective anticancer agents. Despite the success of the first on the market proteasome inhibitor bortezomib in chemotherapy, alternative clinically useful proteasome inhibitors are still urgently needed as bortezomib therapy causes severe side effects and is limited by arising drug resistance. Experience from previous proteasome inhibitor studies has thereby demonstrated that the identification of proteasome inhibitor structures with suitable pharmacological properties i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…88 The letter n denotes the number of monomers in the monocyclic polymer. RGD β-lactam peptidomimetics that induce differential gene expression in human endothelial cells, 49 G-quadruplex ligands for anticancer therapeutics, 50 the excellent tumor uptake and pharmacokinetics of 64 Cu-labeled cyclic RGD peptide dimers with Gly and PEG linkers, 51 macrocyclic lactams as potent Hsp90 inhibitors with excellent tumor exposure and extended biomarker activity, 52,53 proteasome inhibitors, 54 inhibitors of HIV-1 capsid-human lysyl-tRNA synthetase, 55 macrocyclic lactams inspired on the skeleton of natural products with anticancer properties, 56 etc. Besides the considered biomedical applications, macrocyclic structures have found important applications in other fields such as chemical analysis 57,58 or nanotechnology.…”
Section: Macrocyclic Compounds Andmentioning
confidence: 99%
“…88 The letter n denotes the number of monomers in the monocyclic polymer. RGD β-lactam peptidomimetics that induce differential gene expression in human endothelial cells, 49 G-quadruplex ligands for anticancer therapeutics, 50 the excellent tumor uptake and pharmacokinetics of 64 Cu-labeled cyclic RGD peptide dimers with Gly and PEG linkers, 51 macrocyclic lactams as potent Hsp90 inhibitors with excellent tumor exposure and extended biomarker activity, 52,53 proteasome inhibitors, 54 inhibitors of HIV-1 capsid-human lysyl-tRNA synthetase, 55 macrocyclic lactams inspired on the skeleton of natural products with anticancer properties, 56 etc. Besides the considered biomedical applications, macrocyclic structures have found important applications in other fields such as chemical analysis 57,58 or nanotechnology.…”
Section: Macrocyclic Compounds Andmentioning
confidence: 99%
“…It is reported that macrocyclic indole derivatives can demonstrate favorable druglike properties [120,121], including good solubility, increased lipophilicity, enhanced membrane penetration, improved metabolic stability, and good oral bioavailability with desirable pharmacokinetic and pharmacodynamic properties [122,123]. Compound 25 (TMC647055), the 17-membered macrocyclic indole derivative, is currently being evaluated in phase II clinical trials.…”
Section: Prospectivementioning
confidence: 99%
“…Among chemically synthesized pharmaceutical drugs, macrocyclic compounds with a ring of 12 or more atoms [2] are generally favored for synthesizing potential anticancer derivatives, mainly in the chemical, biological, and medical sectors [3][4][5]. Macrocyclic derivatives include peptideand non-peptide-derived compounds, synthesized peptides, and macrocyclic derivatives [6].…”
Section: Introductionmentioning
confidence: 99%